The significance of territory size in colonial nesting geese---an hypothesis - Ryder, John P (Wildfowl, 1975)
Three possible alternatives are presented to explain the evolution of territory size in geese which nest colonially in the Arctic. The author suggests the size of the territory defended by the gander has evolved in relation to food reserves accumulated before the nesting season. The territory is large enough to provide sufficient supplemental food during the entire nesting season and small enough to enable him to protect the nest site from close-nesting conspecifics. The balance between a large and small territory is realized in the gander spending proportionately more time on the area.